Delta-Connection: A Solution for 3D Object Reconstruction - Anzollini, Guilherme Rossetti (2008)
Given a set of consecutive slices resulting from a non-invasive examining device, there is an expectation to be able to reconstruct the 3D original object regardless if it is a human organ or the channeling of underground petroleum resources. The slices however, identify a set of curves, which need to be properly connected to give rise of a coherent representation of the object. This analysis is made by a correspondence algorithm within a 3D reconstruction software. This paper presents -connection, a simple and flexible algorithm for the correspondence problem. -connection relies on the well-known heuristic approach of proximal curves. Tests have shown that -connection grows linearly with the size of the raw-data (the slices) and can be fine-tuned by a user-defined parameter to produce a 3D model. The heuristic, advantages and limitations of -connection will also be shown in detail.